Penyelesaian Sengketa Perkawinan Izin Poligami Di Pengadilan Agama Dalam Perspektif Hukum Positif - Hesti Juli Yanti; Memet Isa Bahrudin (Yayasan Cendekia Gagayunan Indonesia, 2024)
Polygamy is an issue that continues to be controversial with various pros and cons, every man who wants to have more than one wife must first apply for a polygamy permit. Therefore, this study aims to examine the resolution of marital disputes on polygamy permits in the Religious Courts. This research method uses qualitative research laws that emphasize understanding problems in life, this research is carried out by means of literature study. The results obtained in this study are basically positive law and Islamic law allows polygamy with various conditions and agreements, besides that men must be economically capable, they must also be able to ensure fairness as in Surat An-Nisa verse (3).